Chronic Dislocation of the Distal Interphalangeal Joints - Junki Shiota; Daisuke Kawamura; Norimasa Iwasaki (Journal of Trauma and Injury)
Irreducible dislocation of the distal interphalangeal (DIP) joint is a rare traumatic condition commonly seen in sports injuries. Herein, we present a case with chronic dislocation of the DIP joint caused by high energy trauma accompanied by a fracture of the ipsilateral clavicle. The local deformity resulting from the dislocation can be trivial. Therefore, obtaining radiographs of all the interphalangeal joint injuries, regardless of the findings on inspection, is crucial for accurate diagnosis in the case of high energy trauma. The good functional improvement was obtained by open reduction and temporary wire fixation for 4 weeks.